MERONCE ENTREPRENEURSHIP TRAINING FOR CLASS 4 STUDENTS OF PRIMARY SCHOOL NEGERI 1 LAWANG KIDUL LAWANG KIDUL DISTRICT - Novi (P3M Institut Teknologi Pagar Alam, 2023)
This service activity was carriedd out in Lawang Kidul District at SD Negeri 1. the aim of this actiivity was to equip participants with entrepreneurship knowledge so as to improve the abilities and skills of grade 4 students in training to make motif designs in meronce crafts. This service method is implemented by providing training through lectures and interactive questions and answers. The results are an understanding of entrepreneurship training so that students are able to make bracelet craft from beads using the meronce method.